Material for water system pipe fitting and preparation method thereof
By adding anhydride and amine monomers to the polysulfone and polyphenylsulfone to form imide monomers or polymers, the problem of poor compatibility of polyphenylsulfone and polysulfone alloy materials is solved, and the uniformity of material properties and the reduction of cracking risks are achieved.
Patent Information
- Application Number
- CN202510001947.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-04-11
AI Technical Summary
Polyphenylsulfone and polysulfone alloys have poor compatibility during the preparation process, resulting in uneven materials and prone to cracking.
By adding anhydride monomer and amine monomer as compatibilizers and auxiliary compatibilizers to the polysulfone and polyphenylsulfone, the imide monomer or polymer is generated through the reaction in the extruder, thereby improving the compatibility of the material.
The compatibility between polysulfone and polyphenylsulfone is increased, making the material performance more uniform, and avoiding cracking and fracture after material forming.
Smart Images

Figure BDA0005225559550000031 
Figure BDA0005225559550000041
Abstract
Description
Technical Field
[0001] The invention belongs to the field of polymer materials, and in particular relates to a material for water system pipe fittings and a preparation method thereof. Background Art
[0002] Commonly used pipe fittings for water treatment and transportation systems include copper alloys and polypropylene. However, the above materials have some disadvantages. For example, copper alloys often contain metal ions such as lead, which are harmful to the human body. In places where there are corners in polypropylene elbows and tees, it is easy to breed algae and other microorganisms over time. With the emphasis on health by humans, in recent years, countries such as Japan and South Korea have gradually used polybutylene or polyester resin pipes or elbows instead of polypropylene. European and American countries have gradually begun to use sulfone polymers or sulfone polymer alloys and high-density polyethylene as materials for water treatment and transportation pipe fittings. High-density polyethylene is used to prepare the main body of the pipe, which has the characteristics of heat resistance, low microbial growth, and low thermal expansion coefficient; sulfone polymers are used to prepare elbows, tees and other pipe connections, which have the characteristics of high strength, resistance to water flow impact, and low microbial growth. In recent years, the production and sales volume of sulfone polymers for the preparation of water system pipe fitting connection materials has gradually expanded. Polyphenylsulfone is usually used to produce the water system connector. However, polyphenylsulfone is expensive and has high material costs. Therefore, polyphenylsulfone and polysulfone alloys can usually be used to replace polyphenylsulfone to reduce costs.
[0003] However, during the preparation of polyphenylsulfone / polysulfone alloy, it was found that polyphenylsulfone and polysulfone are not compatible. Both polysulfone and polyphenylsulfone are transparent materials, but the material extruded by blending the two is turbid and opaque, indicating that the two are not compatible. As a result, the problem of uneven alloy material will occur. Usually the color of pipe fittings is black or white. Although the dyed material can cover up the problem of material turbidity, it cannot cover up the large performance fluctuations when the material is tested for mechanical properties. This material defect will cause the material to crack during use after injection molding. Summary of the invention
[0004] One of the purposes of the present invention is to provide a polysulfone / polyphenylsulfone material, which can solve the problem of cracking of low-cost sulfone polymer alloy water system materials during use.
[0005] In order to achieve the above-mentioned invention object, the present invention adopts the following technical scheme:
[0006] A sulfone polymer alloy material, comprising the following components:
[0007] 5 to 45 parts of polysulfone substrate, preferably 10 to 30 parts,
[0008] 46 to 88.57 parts of polyphenylsulfone substrate, preferably 65.51 to 85.9 parts,
[0009] 0.2 to 3.4 parts of compatibilizer, preferably 0.29 to 2.2 parts,
[0010] The auxiliary compatibilizer is 0.1 to 2.2 parts, preferably 0.18 to 2 parts.
[0011] In one embodiment of the present invention, the polysulfone substrate has a weight average molecular weight of 70,000 to 90,000, preferably a molecular weight of 72,000 to 85,000, and more preferably one or more of BASF S2010, BASF S3010, Solvay R3500, Solvay R1700, and Wanhua Chemical U4070.
[0012] In one embodiment of the present invention, the polyphenylsulfone substrate has a weight average molecular weight of 70,000 to 90,000, preferably a molecular weight of 75,000 to 83,000, and more preferably one or more of BASF P2010, BASF P3010, Solvay P5000, Solvay P5800, and Wanhua Chemical P6070.
[0013] In one embodiment of the present invention, the compatibilizer is an anhydride monomer, preferably an aromatic dianhydride, more preferably one or more of 3,3',4,4'-diphenyl ether dianhydride, 3,3',4,4'-dibenzophenone dianhydride, pyromellitic acid dianhydride, phthalic anhydride, and 3,3',4,4'-triphenyl diether dianhydride.
[0014] In one embodiment of the present invention, the auxiliary compatibilizer is an amine monomer, preferably an aromatic diamine, more preferably one or more of m-phenylenediamine, 4,4'-diaminodiphenyl ether, and p-phenylenediamine.
[0015] The present invention uses a compatibilizer and an auxiliary compatibilizer to compatibilize polysulfone and polyphenylsulfone, thereby increasing the compatibility of the two. The compatibilizer and the auxiliary compatibilizer are anhydrides and amines, which react in an extruder after mixing to partially generate low-molecular-weight imide monomers or polymers. The solubility parameter range of the imide monomers and oligomers is relatively wide, which can play a role in compatibilizing polysulfone and polyphenylsulfone, thereby reducing the problem of uneven dispersion of polysulfone and polyphenylsulfone.
[0016] The compatibilizer and auxiliary compatibilizer in the present invention react in the extruder to generate imide polymer or its monomer, but this type of material is expensive, so it is not conducive to reducing costs. However, the addition of imide polymer will also increase the volume, toughness and heat resistance of polysulfone and polyphenylsulfone, which is also beneficial to the material. By testing the absorption peak of the imide characteristic group in the material, it can be determined whether imide substances are added to the material.
[0017] In a preferred embodiment of the present invention, the sulfone polymer alloy material is added with toner, lubricant, primary antioxidant, and auxiliary antioxidant. The above additives are conventional additives in the art, and those skilled in the art can select specific substances and dosages as needed.
[0018] In a preferred embodiment of the present invention, the toner is black inorganic toner and / or organic toner, preferably carbon black and / or black iron oxide; preferably, the toner addition amount is 0.3 to 3 parts, preferably 0.5 to 2.7 parts.
[0019] In a preferred embodiment of the present invention, the lubricant is one or more of polyol, stearate, and polyolefin lubricants, preferably one or more of pentaerythritol stearate, polyethylene glycol 4000, polyethylene glycol 6000, and polyethylene wax; preferably, the lubricant is added in an amount of 0.16 to 0.46 parts, preferably 0.19 to 0.3 parts.
[0020] In a preferred embodiment of the present invention, the primary antioxidant is a hindered phenol antioxidant, preferably one or more of 1076, H3311, AO3352, 1010, and hydroquinone; preferably, the addition amount of the primary antioxidant is 0.12 to 0.43 parts, preferably 0.31 to 0.43 parts.
[0021] In a preferred embodiment of the present invention, the auxiliary antioxidant is a phosphite antioxidant, preferably one or more of PEPQ, 9228, 168, and triphenyl phosphite; preferably, the addition amount of the main antioxidant is 0.1 to 0.5 parts, preferably 0.2 to 0.4 parts.
[0022] Another object of the present invention is to provide a method for preparing the sulfone polymer alloy material.
[0023] A method for preparing a sulfone polymer alloy material, wherein the material is the above-mentioned sulfone polymer alloy. The preparation method comprises mixing raw materials, and then performing melt extrusion and pelletizing in an extruder to obtain the sulfone polymer alloy material; preferably, the raw materials are fed into the extruder through a main feed and more than one side feed.
[0024] In one embodiment of the present invention, in the preparation method, the aspect ratio of the extruder is 36-44.
[0025] In one embodiment of the present invention, in the preparation method, the temperature of the initial section of the extruder is 80-290°C, the temperature of the middle section is 310-320°C, the temperature of the tail section is 330-345°C, and the temperature of the head is 335-355°C; the vacuum degree of the tail section is -0.55 to -0.95MPa.
[0026] In one embodiment of the present invention, in the preparation method, the screw speed of the extruder is 150-350 rpm.
[0027] Another object of the present invention is to provide a use of the sulfone polymer alloy material.
[0028] A use of a sulfone polymer alloy material, wherein the material is the above-mentioned sulfone polymer alloy material, or a material prepared by the above-mentioned preparation method, and the material is used for processing pipes, preferably for processing liquid transport pipes.
[0029] Another object of the present invention is to provide a pipe.
[0030] A pipe is obtained by processing the sulfone polymer alloy material or the sulfone polymer alloy material prepared by the preparation method.
[0031] Compared with the prior art, the positive effects of the present invention are:
[0032] The use of dianhydride compatibilizer and diamine auxiliary compatibilizer increases the compatibility of polysulfone and polyphenylsulfone materials, making the performance of the materials more uniform, thereby avoiding cracking and breaking of the materials after molding. DETAILED DESCRIPTION
[0033] The raw materials used in this experiment are as follows:
[0034]
[0035]
[0036] Mechanical properties test methods
[0037] The spline mechanical property testing method described in the embodiment of the present invention is "GB / T 1843-2008 Determination of the impact strength of plastic cantilever beam".
[0038] Example 1
[0039] Main raw material of the composition: polyphenylsulfone (R5000) 85.9wt%
[0040] Mixed material: polysulfone (S3010) 5wt%, black toner (carbon black) 1.8wt%, lubricant (pentaerythritol stearate) 0.3wt%, compatibilizer (3,3',4,4'-diphenyl ether dianhydride) 2wt%, auxiliary compatibilizer (m-phenylenediamine) 1.5wt%, primary antioxidant (1076) 3wt%, auxiliary antioxidant (PEPQ) 0.5wt%. The above materials are mixed evenly and named as material A.
[0041] Material processing method: feed the main material of polyphenylsulfone into the extruder from the main feed. Divide material A into 2 parts, of which 1 / 3 is fed into the extruder from the main feed, and 2 / 3 is fed into the extruder from the side feed of the 6th section; the aspect ratio of the extruder is 36, the temperature of the initial section (1-3 zones) is 90, 260, 290℃; the temperature of the middle section (4-7 zones) is 310, 310, 320, 320℃; the temperature of the tail section (8-9) is 330, 330, and the temperature of the die head is 335℃; the vacuum degree of the tail section is -0.55MPa; the screw speed is 150rpm; the processing capacity is 30kg / h. The extruded material is water-cooled or air-cooled and pelletized to make the finished product.
[0042] The material was tested for unnotched impact strength after injection molding. Five specimens were tested and the data were: 166kJ / ㎡, 172kJ / ㎡, 160kJ / ㎡, 168kJ / ㎡, and 173kJ / ㎡ respectively.
[0043] Example 2
[0044] Main raw material components of the composition: polyphenylsulfone (P3010) 88.57wt%;
[0045] Mixed materials: polysulfone (U1700) 5wt%, black toner (carbon black) 0.3wt%, lubricant (polyethylene glycol 4000) 0.16wt%, compatibilizer (3,3',4,4'-benzophenone dianhydride) 0.29wt%, auxiliary compatibilizer (4,4'-diaminodiphenyl ether) 0.18wt%, primary antioxidant (1010) 0.4wt%, auxiliary antioxidant (9228) 0.1wt%. The above materials are mixed evenly and named as material A.
[0046] Material processing method: feed the main material of polyphenylsulfone into the extruder from the main feed. Divide material A into 3 parts, of which 1 / 3 is fed into the extruder from the main feed, 1 / 3 is fed into the extruder from the side feed of the 6th section, and 1 / 3 is fed into the extruder from the side feed of the 9th section; the aspect ratio of the extruder is 44, the temperature of the initial section (1-3 zones) is 80, 270, 280℃; the temperature of the middle section (4-7 zones) is 310, 310, 320, 320℃; the temperature of the tail section (8-10) is 330, 340, 340, 340℃, and the temperature of the die head is 345℃; the vacuum degree of the tail section is -0.65MPa; the screw speed is 200rpm; the processing capacity is 50kg / h. The extruded material is water-cooled or air-cooled and pelletized to make the finished product.
[0047] The material was tested for unnotched impact strength after injection molding. Five specimens were tested and the results were: 172kJ / ㎡, 178kJ / ㎡, 180kJ / ㎡, 173kJ / ㎡, and 175kJ / ㎡.
[0048] Example 3
[0049] Main raw material components of the composition: polyphenylsulfone (P2010) 74.56wt%;
[0050] Mixed materials: polysulfone (S2010) 5wt%, black toner (iron oxide black) 0.5wt%, lubricant (polyethylene glycol 6000) 0.22wt%, compatibilizer (pyromellitic anhydride) 2.2wt%, auxiliary compatibilizer (4,4'-diaminodiphenyl ether) 2.0wt%, primary antioxidant (hydroquinone) 0.12wt%, auxiliary antioxidant (168) 0.4wt%. The above materials are mixed evenly and named as material A.
[0051] Material processing method: feed the main material of polyphenylsulfone into the extruder from the main feed. Divide material A into 2 parts, of which 1 / 2 is fed into the extruder from the main feed, and 1 / 2 is fed into the extruder from the side feed of section 6; the aspect ratio of the extruder is 36, the temperature of the initial section (1-3 zones) is 120, 270, 280℃; the temperature of the middle section (4-7 zones) is 310, 310, 320, 320℃; the temperature of the tail section (8-9) is 330, 335℃, and the temperature of the die head is 340℃; the vacuum degree of the tail section is -0.75MPa; the screw speed is 300rpm; the processing capacity is 300kg / h. The extruded material is water-cooled or air-cooled and pelletized to make the finished product.
[0052] The material was tested for unnotched impact strength after injection molding. Five specimens were tested and the results were: 163kJ / ㎡, 154kJ / ㎡, 156kJ / ㎡, 148kJ / ㎡, and 155kJ / ㎡.
[0053] Example 4
[0054] Main raw material components of the composition: polyphenylsulfone (R5800) 65.41wt%;
[0055] Mixed materials: polysulfone (U3500) 5wt%, black toner (iron oxide black) 3wt%, lubricant (polyethylene wax) 0.46wt%, compatibilizer (phthalic anhydride) 0.2wt%, auxiliary compatibilizer (p-phenylenediamine) 0.1wt%, primary antioxidant (H3311) 0.43wt%, auxiliary antioxidant (168) 0.3wt%. The above materials are mixed evenly and named as material A.
[0056] Material processing method: feed the main material of polyphenylsulfone into the extruder from the main feed. Divide material A into 2 parts, of which 2 / 3 is fed into the extruder from the main feed, and 1 / 3 is fed into the extruder from the side feed of the 6th section; the aspect ratio of the extruder is 40, the temperature of the initial section (1-3 zones) is 180, 250, 280℃; the temperature of the middle section (4-7 zones) is 310, 310, 320, 320℃; the temperature of the tail section (8-10) is 330, 330, 340℃, and the temperature of the die head is 345℃; the vacuum degree of the tail section is -0.95MPa; the screw speed is 250rpm; the processing capacity is 500kg / h. The extruded material is water-cooled or air-cooled and pelletized to make the finished product.
[0057] The material was tested for unnotched impact strength after injection molding. Five specimens were tested and the results were: 196kJ / ㎡, 189kJ / ㎡, 185kJ / ㎡, 179kJ / ㎡, and 194kJ / ㎡.
[0058] Example 5
[0059] Main raw material components of the composition: polyphenylsulfone (P6070) 46wt%;
[0060] Mixed materials: polysulfone (U4070) 45wt%, black toner (carbon black) 2.7wt%, lubricant (polyethylene glycol 4000) 0.19wt%, compatibilizer (3,3',4,4'-triphenyl diether dianhydride) 3.4wt%, auxiliary compatibilizer (4,4'-diaminodiphenyl ether) 2.2wt%, primary antioxidant (AO3352) 0.31wt%, auxiliary antioxidant (triphenyl phosphite) 0.2wt%. The above materials are mixed evenly and named as material A.
[0061] Material processing method: feed the main material of polyphenylsulfone into the extruder from the main feed. Divide material A into 2 parts, of which 1 / 3 is fed into the extruder from the main feed, and 2 / 3 is fed into the extruder from the side feed of the 6th section; the aspect ratio of the extruder is 40, the temperature of the initial section (1-3 zones) is 230, 270, 280℃; the temperature of the middle section (4-7 zones) is 310, 310, 320, 320℃; the temperature of the tail section (8-10) is 330, 340, 345℃, and the temperature of the die head is 355℃; the vacuum degree of the tail section is -0.85MPa; the screw speed is 350rpm; the processing capacity is 100kg / h. The extruded material is water-cooled or air-cooled and pelletized to make the finished product.
[0062] The material was tested for unnotched impact strength after injection molding. Five specimens were tested and the data were: 156kJ / ㎡, 153kJ / ㎡, 159kJ / ㎡, 166kJ / ㎡, and 163kJ / ㎡ respectively.
[0063] Comparative Example 1
[0064] Compared with Example 1, the only difference is that no compatibilizer is added, and the rest is the same as Example 1.
[0065] After all materials are mixed, they are added to the extruder from the main feed and side feed. The material is tested for unnotched impact strength by injection molding. The data of five specimens are: 86kJ / ㎡, 92kJ / ㎡, 160kJ / ㎡, 48kJ / ㎡, and 73kJ / ㎡.
[0066] Comparative Example 2
[0067] Compared with Example 1, the only difference is that no auxiliary compatibilizer is added, and the rest is the same as Example 1.
[0068] The material was tested for unnotched impact strength by injection molding. Five specimens were tested, and the data were 86 kJ / ㎡, 92 kJ / ㎡, 160 kJ / ㎡, 48 kJ / ㎡, and 73 kJ / ㎡, respectively. From the test data, without using auxiliary compatibilizer, but using the main feeding and side feeding split feeding process for processing, the data fluctuation of the unnotched impact strength of the material is larger than that of Example 1, and the data average value is smaller than that of Example 1.
[0069] Comparative Example 3
[0070] Compared with Example 1, the only difference is that all the raw materials are added as main feed, and the rest is the same as Example 1.
[0071] The formula in Example 1 remains unchanged, and all material A is added to the extruder from the main feed, and other conditions are the same as in Example 1. The material is tested for unnotched impact strength by injection molding, and the data of five specimens are: 126kJ / ㎡, 92kJ / ㎡, 130kJ / ㎡, 118kJ / ㎡, and 153kJ / ㎡. From the test data, the material is completely processed by the main feed process, and the data fluctuation of the unnotched impact strength of the material is larger than that of Example 1, and the average value of the data is smaller than that of Example 1.
[0072] From the test data, it can be seen that only auxiliary compatibilizers are used, and all materials are added to the extruder from the main feed and the side feed after mixing. The data fluctuation of the material's unnotched impact strength is larger than that of Example 1, and the data average value is smaller than that of Example 1.
[0073] The above comparative examples show that the problem of poor compatibility between polysulfone and polyphenylsulfone can be effectively solved by adding a compatibilizer and an auxiliary compatibilizer and by splitting the feeding.
[0074] Those skilled in the art will appreciate that, based on the teachings of this specification, some modifications or adjustments may be made to the present invention, and these modifications or adjustments should also be within the scope defined by the claims of the present invention.
Claims
1. A sulfone polymer alloy material, characterized in that: The material comprises the following components: 5 to 45 parts of polysulfone substrate, preferably 10 to 30 parts, 46 to 88.57 parts of polyphenylsulfone substrate, preferably 65.51 to 85.9 parts, 0.2 to 3.4 parts of compatibilizer, preferably 0.29 to 2.2 parts, The auxiliary compatibilizer is 0.1 to 2.2 parts, preferably 0.18 to 2 parts.
2. The material according to claim 1, characterized in that The polysulfone substrate has a weight average molecular weight of 70,000 to 90,000, preferably 72,000 to 85,000, and more preferably one or more of BASF S2010, BASF S3010, Solvay R3500, Solvay R1700, and Wanhua Chemical U4070.
3. The material according to claim 1 or 2, characterized in that The polyphenylsulfone substrate has a weight average molecular weight of 70,000 to 90,000, preferably a molecular weight of 75,000 to 83,000, and more preferably one or more of BASF P2010, BASF P3010, Solvay P5000, Solvay P5800, and Wanhua Chemical P6070.
4. The material according to any one of claims 1 to 3, characterized in that The compatibilizer is an anhydride monomer, preferably an aromatic dianhydride, more preferably one or more of 3,3',4,4'-diphenyl ether dianhydride, 3,3',4,4'-benzophenone dianhydride, pyromellitic acid dianhydride, phthalic anhydride, and 3,3',4,4'-triphenyl diether dianhydride.
5. The material according to any one of claims 1 to 4, characterized in that The auxiliary compatibilizer is an amine monomer, preferably an aromatic diamine, more preferably one or more of m-phenylenediamine, 4,4'-diaminodiphenyl ether, and p-phenylenediamine.
6. A method for preparing a sulfone polymer alloy material, wherein the material is the sulfone polymer alloy according to any one of claims 1 to 5, characterized in that: The preparation method comprises mixing the raw materials, and then performing melt extrusion and pelletizing in an extruder to obtain a sulfone polymer alloy material; Preferably, the raw materials are fed into the extruder via a main feed and one or more side feeds.
7. The preparation method according to claim 6, characterized in that: In the preparation method, the aspect ratio of the extruder is 36 to 44; And / or, in the preparation method, the temperature of the initial section of the extruder is 80-290°C, the temperature of the middle section is 310-320°C, the temperature of the tail section is 330-345°C, and the temperature of the die head is 335-355°C; the vacuum degree of the tail section is -0.55--0.95MPa; And / or, in the preparation method, the screw speed of the extruder is 150 to 350 rpm.
8. Use of a sulfone polymer alloy material, wherein the material is the sulfone polymer alloy material according to any one of claims 1 to 5, or is a material prepared by the preparation method according to claim 6 or 7, and the material is used for processing pipes, preferably for processing liquid transport pipes.
9. A pipe, wherein the pipe is made from the sulfone polymer alloy material according to any one of claims 1 to 5, or the sulfone polymer alloy material prepared by the preparation method according to claim 6 or 7.